2016
DOI: 10.1055/s-0035-1561478
|View full text |Cite
|
Sign up to set email alerts
|

Fulvalene Derivatives Containing a Tetrabenzofluorene Unit: New Nonplanar Fulvalenes with High Electron Affinity

Abstract: c,g,i]fluoren-17-one possessing a nonplanar, helicene-like structure was efficiently prepared by aerial oxidation of 17H-tetrabenzo[a,c,g,i]fluorene under mild basic conditions. A quinone methide and an unsymmetrical fulvalene containing a tetrabenzofluorene unit were synthesized from the ketone. Treatment of 17-bromotetrabenzo [a,c,g,i]fluorene with a base afforded a symmetric fulvalene as an air-sensitive blue solid. Electrochemical analyses revealed that these compounds have high electron affinities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The studied 9,9’-BF based compounds were strategically designed and should exhibit interesting electrochemical properties (vide infra). Although the synthesis and some properties of 3 have been reported 29 , the structure was confirmed for the first time in this study using X-ray crystallography. Importantly, we found that the configurations of two semi-rigid helical substructures significantly affect the structural parameters and properties, which are discussed in the following sections.…”
Section: Introductionmentioning
confidence: 52%
“…The studied 9,9’-BF based compounds were strategically designed and should exhibit interesting electrochemical properties (vide infra). Although the synthesis and some properties of 3 have been reported 29 , the structure was confirmed for the first time in this study using X-ray crystallography. Importantly, we found that the configurations of two semi-rigid helical substructures significantly affect the structural parameters and properties, which are discussed in the following sections.…”
Section: Introductionmentioning
confidence: 52%
“…Moreover, its alkyl and phenylated derivatives have shown interesting fluorescence attributes in solution and in solid films [20] . Lastly, its fulvalene derivative and oxo forms performed well as electron acceptors [21] . In general, the synthesis of tetrabenzofluorene and its derivatives involves multiple synthetic steps [15–19,22] .…”
Section: Introductionmentioning
confidence: 99%
“…[20] Lastly, its fulvalene derivative and oxo forms performed well as electron acceptors. [21] In general, the synthesis of tetrabenzofluorene and its derivatives involves multiple synthetic steps. [15][16][17][18][19]22] In contrast, Dyker and co-workers demonstrated an efficient route to fluoreno [5]helicenes in one step by the solution-phase cyclodehydrogenation of pentaarylcyclopentadiene precursor (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%